Youth without representation : the absence of young adults in parliaments, cabinets, and candidacies - Stockemer, Daniel; Sundström, Askel (University of Michigan Press, 2022)
Officeholders in contemporary parliaments and cabinets are more likely than not to be male, wealthy, middle-aged or older, and from the dominant ethnicity, whereas young adults have an insufficient presence in political office. Young adults--those aged 35 years or under--comprise a mere ten percent of all parliamentarians globally, and three percent of all cabinet members. Compared to their presence in the world's population, this age group faces an underrepresentation of one to three in parliament and one to ten in cabinet. In this book, Stockemer and Sundström provide a holistic account of youths' marginalization in legislatures, cabinets, and candidacies for office through a comparative lens. They argue that youths' underrepresentation in political office constitutes a democratic deficit and provide ample evidence for why they think that youth must be present in politics at much higher rates. They further embed this book within what they label a vicious cycle of political alienation, which involves the declining political sophistication of the young, their waning electoral participation, and their insufficient of representation in office. Empirically, the authors combine a global focus with in-depth studies, discussing the country-level, party-level, and individual-level factors that bar young adults' entry to positions of political power. This is the first comprehensive book on youth representation and it has relevance for those broadly interested in issues of representation, democracy, inequality, and comparative politics.